The Role of Somatic Mutations in Ischemic Stroke: CHIP’s Impact on Vascular Health - Aiman Kinzhebay; Amankeldi A. Salybekov (Neurology International)
Clonal hematopoiesis of indeterminate potential (CHIP) is increasingly recognized as a significant contributor to ischemic stroke and other cardiovascular diseases due to its association with somatic mutations in hematopoietic cells. These mutations, notably in genes like DNMT3A, TET2, and JAK2, induce pro-inflammatory and pro-atherosclerotic processes, promoting vascular damage and stroke risk. With the prevalence of CHIP rising with age, its presence correlates with higher mortality and morbidity rates in ischemic stroke patients. This article explores the mechanisms through which CHIP influences vascular aging and stroke, emphasizing its potential as a biomarker for early risk stratification and a target for therapeutic intervention. The findings highlight the necessity of integrating CHIP status in clinical evaluations to better predict outcomes and personalize treatment strategies in stroke management.